CHANGES OF THE OPTICAL PROPERTIES OF TOP-GRADE FLOUR (SEMOLINA) FROM DURUM WHEAT DURING ITS RIPENING - T. S. Steinberg; E. P. Meleshkina; O. G. Shvedova; O. V. Morozova; N. S. Zhiltsova (Пищевые системы)
Using the rapid method of digital image analysis by the developed scanning flour analyzer the optical properties of flour (semolina) obtained in laboratory and production conditions from durum wheat of three years of harvest (2017–2019), namely the «yellowness» indicator and the color characteristic in the blue part of the spectrum, were determined. The semolina color was also evaluated by the Konica Minolta CR-410 colorimeter. It is established that the «yellowness» indicator and the color characteristic in the blue part of the spectrum did not change within the first 5 to 6 days after grinding. The change of these indicators for all the samples is observed in the period from 6 to 20 days after grinding, there with the «yellowness» indicator decreased by 25 to 40 relative units, the color characteristic in the blue part of the spectrum increased on average by 133,75 relative units. Over the next three months, there was no change of color (by both indicators). In the course of experimental work the optical properties change depending upon carotenoids content of flour (semolina) during its ripening was shown. The correlation dependence between the «yellowness» indicator of flour (semolina) and its carotenoids content is characterized by a high approximation coefficient. The dependence of the color characteristic of flour in the blue part of the spectrum on the content of carotenoids is characterized by an approximation coefficient equal to 0.9358, and is described as a polynomial equation. It shows, that with a low carotenoid content, the considered indicator is higher by an average of 1100 relative units compared to the color of samples with a carotenoid content from 0.70 to 1.21 mcg/g. At that during storage the optical properties of flour variety with the lowest carotenoids content remained practically the same. During 78 days of storage, there was no significant change of color characteristics of the industrial flour samples, studied from the eleventh day after grinding — 5–8 times higher than the average repeatability of the measurement results.